2020
DOI: 10.3390/rs12060914
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fine Particulate Matter (PM2.5) in the Greater London Area: An Ensemble Approach using Machine Learning Methods

Abstract: Estimating air pollution exposure has long been a challenge for environmental health researchers. Technological advances and novel machine learning methods have allowed us to increase the geographic range and accuracy of exposure models, making them a valuable tool in conducting health studies and identifying hotspots of pollution. Here, we have created a prediction model for daily PM2.5 levels in the Greater London area from 1st January 2005 to 31st December 2013 using an ensemble machine learning approach in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…The spatio-temporal ML models presented here demonstrated comparable predictive performance to similar methods applied in other countries, based either on single-learner ML models [de Hoogh et al, 2018; Stafoggia et al, 2019], ensemble ML models [Chen et al, 2018; Di et al, 2019; Yazdi et al, 2020], or generalised additive models (GAM) [Kloog et al, 2015]. Yazdi et al (2020) developed an ensemble ML model (composed by RF, Deep Neural Network, GAM, Gradient Boosting, K-nearest Neighbour) to estimate PM 2.5 for Greater London, reaching mean 2005-2013 CV spatial-R 2 of 0.396. Using 2008-2013 period, this study reached CV spatial-R 2 of 0.637 for the whole Great Britain.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The spatio-temporal ML models presented here demonstrated comparable predictive performance to similar methods applied in other countries, based either on single-learner ML models [de Hoogh et al, 2018; Stafoggia et al, 2019], ensemble ML models [Chen et al, 2018; Di et al, 2019; Yazdi et al, 2020], or generalised additive models (GAM) [Kloog et al, 2015]. Yazdi et al (2020) developed an ensemble ML model (composed by RF, Deep Neural Network, GAM, Gradient Boosting, K-nearest Neighbour) to estimate PM 2.5 for Greater London, reaching mean 2005-2013 CV spatial-R 2 of 0.396. Using 2008-2013 period, this study reached CV spatial-R 2 of 0.637 for the whole Great Britain.…”
Section: Discussionmentioning
confidence: 77%
“…Country-wide maps generated by emission-dispersion models are usually available at coarser spatial or temporal resolution [DEFRA, 2020; EMEP4UK, 2020; Savage et al, 2013, and generally they show lower small-scale accuracy when tested against observed monitoring data [Hood et al, 2018; Lin et al, 2017]. The spatio-temporal ML models presented here demonstrated comparable predictive performance to similar methods applied in other countries, based either on single-learner ML models [de Hoogh et al, 2018; Stafoggia et al, 2019], ensemble ML models [Chen et al, 2018; Di et al, 2019; Yazdi et al, 2020], or generalised additive models (GAM) [Kloog et al, 2015]. Yazdi et al (2020) developed an ensemble ML model (composed by RF, Deep Neural Network, GAM, Gradient Boosting, K-nearest Neighbour) to estimate PM 2.5 for Greater London, reaching mean 2005-2013 CV spatial-R 2 of 0.396.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As all the methods used are data driven model may be inclusion of more number of data may have provided better accuracy. Even though the results obtained by using this hybrid method for prediction of PM2.5 is not too high as 0.97 obtained by (Amanollahi and Ausati 2020) still, comparatively better than some of the results obtained by (Joharestani et al 2019;Yazdi et al 2020). Thus, this method can easily be implemented because of its robustness as it has can be used for prediction as well as spatial representation of PM2.5 compared to other approaches used.…”
Section: Descriptive Statisticsmentioning
confidence: 77%
“…(Joharestani et al 2019) has implemented random forest, extreme gradient boosting, and machine learning (ML) approaches along with 23 features and obtained better prediction results. (Yazdi et al 2020) has used and compared various machine learning approach and found out that the random forest (RF) technique performs the best in comparison with all other method used. (Shahriar et al 2020) has used the linear-support vector machine (L-SVM), medium Gaussian-support vector machine (M-SVM), Gaussian process regression (GPR), arti cial neural network (ANN), random forest regression (RFR), and a time series model namely PROPHE and found out that GPR and ANN perform better in (Ventura et al 2019) has applied two models, Holt-Winters (HW) and arti cial neural network (ANN), using PM 2.5 concentration time series and found ANN performs better with less RMSE error.…”
Section: Introductionmentioning
confidence: 99%